WOMEN EMPOWERMENT THROUGH SELF HELP GROUPS (A Study with Reference to East Godavari District of Andhra Pradesh State) - G. Chandrakala; Prof. S. Teki (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
Women participation in Self Help Groups created a wonderful impact upon the life pattern and style of poor women. They empowered at various levels not only as individuals but also as members of the family, community members and the society as whole. They gather for the purpose of solving their problems which are common through self-help and mutual help. It enhanced the general knowledge, awareness and improves their bargaining capacity of the rural women. It is a best technique to remove poverty and improve the women entrepreneurship and financial support in overall India. The present paper confines itself to Women Empowerment through the Self Help Groups w.r.t. East Godavari District of Andhra Pradesh State. In present study simple statistical tools were adopted based on the analysis of women empowerment through Self Help Groups in East Godavari District, the major findings of this study there is a positive impact of Self Help Groups on Women empowerment in East Godavari District of Andhra Pradesh State.